Household Gods - Tarrand, Judith and Harry Turtledove (New York A Tom Doherty Associates Book, 2000)
Nicole Gunther-Perrin is a modern young professional, proud of her legal skills but weary of the daily grind, of childcare, and of sexist coworkers and her deadbeat ex-husband. Then after one exceptionally awful day, she awakens to find herself in a different life, that of a widowed tavernkeeper on the Roman frontier around A.D. 170.
Keywords: Fiction